Steering epistemic access in higher education in South Africa : institutional dilemmas - Cross, Michael, 1952- (Serie Estudios e investigaciones (Consejo Latinoamericano de Ciencias Sociales), 2018)
This book utilises a broadly critical cultural approach to explain access and retention. In recent years, the use of cultural approaches has made a significant contribution to how we understand societies and particularly social institutions undergoing transition. The impact of these approaches is evident in the social sciences and in interdisciplinary fields such as education, where different dimensions and perspectives within respective cultural approaches have been applied to a variety of topics.